Application of four different football match analysis systems: A comparative study - Randers, M. B.; Mujika, I.; Hewitt, A.; Santisteban, J.; Bischoff, R.; Solano, R.; Zubillaga, A.; Peltola, E.; Krustrup, P.; Mohr, M. (Journal of Sports Sciences, 2010)
Using a video-based time-motion analysis system, a semi-automatic multiple-camera system, and two commercially available GPS systems (GPS-1; 5 Hz and GPS-2; 1 Hz), we compared activity pattern and fatigue development in the same football match. Twenty football players competing in the Spanish second and third divisions participated in the study. Total distance covered during the match for the four systems was as follows: 10.83 ± 0.77 km (semi-automatic multiple-camera system, n = 20), 9.51± 0.74 km (video-based time-motion analysis system, n = 17), 10.72 ± 0.70 km (GPS-1, n = 18), and 9.52 ± 0.89 km (GPS-2, n = 13). Distance covered by high-intensity running for the four systems was as follows: 2.65 ± 0.53 km (semi-automatic multiple-camera system), 1.61 ± 0.37 km (video-based time-motion analysing system), 2.03 ± 0.60 km (GPS-1), and 1.66 ± 0.44 km (GPS-2). Distance covered by sprinting for the four systems was as follows: 0.38 ± 0.18 km (semi-automatic multiple-camera system), 0.42 ± 0.17 km (video-based time-motion analysing system), 0.37 ± 0.19 km (GPS-1), and 0.23 ± 0.16 km (GPS-2). All four systems demonstrated greater (P < 0.05) total distance covered and high-intensity running in the first 15-min period and less (P < 0.05) total distance covered and high-intensity running during the last 15-min period than all other 15-min intervals, with a reduction (P < 0.05) in high-intensity running from the first to the last 15-min period of 46 ± 19%, 37 ± 26%, 50± 26%, and 45 ± 27% for the semi-automatic multiple-camera system, video-based time-motion analysis system, GPS-1, and GPS-2, respectively. Our results show that the four systems were able to detect similar performance decrements during a football game and can be used to study game-induced fatigue. Rather large between-system differences were present in the determination of the absolute distances covered, meaning that any comparisons of results between different match analysis systems should be done with caution.